Avaliação da adesão a medidas para a prevenção de infecções do sítio cirúrgico e efetividade da utilização de luvas cirúrgicas estéreis em um hospital universitário - Camila Sarmento Gama (2013)
Surgical site infections are the most common complications in patients who undergo surgery. The surgical team assumes a fundamental role in preventing these infections before and during surgery, with respect to many aspects of the surgical process including: either with respect to surgical hand antisepsis, surgical attire, patient skin preparation, control of the number of people present in the operating room, people and equipments traffic and excessive talk of professionals within the operating room, moving doors and decision at the time and type of antimicrobial prophylaxis. This research aimed to evaluate pre- and intraoperative recommendations for the prevention of surgical site infections and the integrity of sterile gloves used by surgical teams of the digestive system, cardiovascular and pediatric from hospital in Belo Horizonte. This cross-sectional study was conducted in a large university hospital of Belo Horizonte during the April to September 2013. Data collection was divided into two phases: phase I Integrity assessment of gloves used during surgery; and phase II Was a direct observation and analysis of patients medical records to collect data of: use of attire and accessories by individuals present in the operating room, hair removal, number of people in the room, time that the door remained open, preoperative shower, ASA (American Society of Anesthesiologists) score, wound class and antibiotic prophylaxis, as well as evaluation of potential perforations in surgical gloves, through test described by European standard EN 455-1. The collected data were analyzed with SPSS version 20. A total of 100 surgeries were monitored and with analysis of 1,090 gloves, 131 (12%) of the gloves had perforation detected after surgery, of which 37.5% was recognised by users at the time of the perforation. The preoperative shower on the day of surgery was performed by 91% of patients, occurring 59.3% in hospital and 40.7% at home. Only 2.2 % of patients reported the use of antiseptic agent during the shower. Hair removal was conducted in the operating room for 20% using electric clippers most of the time (65%). The choice for antibiotic prophylaxis was adequate or satisfactory in 68% of procedures, and was administered in less than 60 minutes before the surgical incision in 90.3% of cases. There was an average of 8.1 professionals present during surgery and the operating room door remained opened in 96% of procedures. With respect to the use of attire and accessories by the surgical team, 26.9% of professionals wore goggles; 57.2%, shoe covers; 19.5% properly wore a cap; 99.7%, gowns; 95.8% a mask positioned properly; 100% gloves during surgical procedures; and only one member, used a ring. There was partial compliance by professionals to recommendations for the prevention and control of surgical site infection during the pre-and intraoperative periods. The identification of measures that had low adherence favors the planning of interventions to improve the safety and quality of patient care. In addition, these measures can contribute to audit control practices for the prevention surgical site infections.